2004
DOI: 10.1111/j.1526-4610.2004.4200_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia Due to Pontine Infarction

Abstract: Trigeminal neuralgia (TN) is most commonly caused by vascular compression of the trigeminal nerve root entry zone. Secondary trigeminal neuralgia due to ischemic lesion of the pons is very rare. Here we report a patient with a pontine infarct transecting the central trigeminal pathways resulting with trigeminal neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…These findings indicate that trigeminal neuralgia in cases with vascular compression is due to demyelination. Recently, Peker et al [36] described a case of secondary TN due to pontine infarction which supports the central origin. De Ridder et al [12] supported the central theory and suggested a correlation between the length of the central segment of a cranial nerve and incidence of vascular compression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that trigeminal neuralgia in cases with vascular compression is due to demyelination. Recently, Peker et al [36] described a case of secondary TN due to pontine infarction which supports the central origin. De Ridder et al [12] supported the central theory and suggested a correlation between the length of the central segment of a cranial nerve and incidence of vascular compression.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the involvement of the pontine trigeminal entry zone (which has been implicated in the pathogenesis of trigeminal neuralgia [21] and SUNCT-like headache [22]) may also have led to the attacks of pain and, during severe attacks, to autonomic symptoms by the activation of collaterals of second-order trigeminal neurones to the superior salivatory nucleus. Alternatively, the partial ischemic damage to the spinal trigeminal tract or nucleus (causing ipsilateral facial hypesthesia for pain and temperature) may have led to an aberrant signal transmission to higher-order pain centres.…”
Section: Discussionmentioning
confidence: 98%
“…One could be demyelination, which would cause electrophysiological alterations in the trigeminal system leading to ephaptic transmission, spontaneous firing, and mechanosensitivity, both before and after discharge. 3,4 The other could be the anatomical structure of trigeminal pathways. In general, the spinal trigeminal nucleus that controls the craniocervical part of algesthesia exists more caudal in the brainstem compared with the other nuclei of the trigeminal nerve.…”
Section: Discussionmentioning
confidence: 99%